BrainBase: a curated knowledgebase for brain diseases. Issue Volume 50:Issue D1(2022) (30th October 2021) - Liu, Lin; Zhang, Yang; Niu, Guangyi; Li, Qianpeng; Li, Zhao; Zhu, Tongtong; Feng, Changrui; Liu, Xiaonan; Zhang, Yuansheng; Xu, Tianyi; Chen, Ruru; Teng, Xufei; et al.
Abstract: Brain is the central organ of the nervous system and any brain disease can seriously affect human health. Here we present BrainBase (https://ngdc.cncb.ac.cn/brainbase ), a curated knowledgebase for brain diseases that aims to provide a whole picture of brain diseases and associated genes. Specifically, based on manual curation of 2768 published articles along with information retrieval from several public databases, BrainBase features comprehensive collection of 7175 disease–gene associations spanning a total of 123 brain diseases and linking with 5662 genes, 16 591 drug–target interactions covering 2118 drugs/chemicals and 623 genes, and five types of specific genes in light of expression specificity in brain tissue/regions/cerebrospinal fluid/cells. In addition, considering the severity of glioma among brain tumors, the current version of BrainBase incorporates 21 multi-omics datasets, presents molecular profiles across various samples/conditions and identifies four groups of glioma featured genes with potential clinical significance. Collectively, BrainBase integrates not only valuable curated disease–gene associations and drug–target interactions but also molecular profiles through multi-omics data analysis, accordingly bearing great promise to serve as a valuable knowledgebase for brain diseases.